Design an implementation of a system for magnetoelectric measurements on BiFeO3 nanoparticles as a function of temperature and magnetic field (2019)
Incluye apéndice: Sistema para la medición de efecto magnetoeléctrico en nanopartículas de ferrita de bismuto (Propuesta inicial del proyecto).